Characterization of the Cultivable Endophytic Bacterial Community of Seeds and Sprouts of Cannabis sativa L. and Perspectives for the Application as Biostimulants - Gabriele, Morena; Vitali, Francesco; Chelucci, Elisa; Chiellini, Carolina (Microorganisms (Basel), 2022)
Endophytes are beneficial microorganisms exerting growth-promoting activities in plants; they are most often located within the plant intercellular spaces and can be found in all plant tissues, including roots, leaves, stems, flowers, and seeds. In this work, we investigated the cultivable bacterial community of the seeds and the two-week sprouts of the Cannabis sativa L. cultivar “Futura 75”. Endophytes were genotypically and phenotypically characterized and were exposed to different concentrations of seed extracts to verify their susceptibility. A bacterial strain among all the isolates was selected for germination tests of C. sativa in different experimental conditions. The results revealed the dominance of Firmicutes (Staphylococcus sp.) among the isolated strains. Two strains were different from the others for indole-3-acetic acid (IAA) production and for their resistance patterns towards abiotic and biotic stresses. The Sphingomonas sp. strain Can_S11 (Alphaproteobacteria) showed a potential ability to increase the nutraceutical features of its sprouts, particularly an increase in the polyphenol content and antioxidant activity. None of the isolated strains were susceptible to the seed extracts, which were previously tested as antimicrobial and antibiofilm agents against human pathogenic bacteria. The results open new perspectives for the study of the endophytes of C. sativa as possible biostimulants.